Ferroelectric Polymers: Epitaxially Grown Ferroelectric PVDF‐TrFE Film on Shape‐Tailored Semiconducting Rubrene Single Crystal (Small 22/2018). Issue 22 (28th May 2018) - Lee, Yujeong; Kim, Kang Lib; Kang, Han Sol; Jeong, Beomjin; Park, Chanho; Bae, Insung; Kang, Seok Ju; Park, Youn Jung; Park, Cheolmin
Abstract : In article number1704024, Cheolmin Park and co‐workers successfully fabricate epitaxially grown ferroelectric polymer film on semiconducting rubrene single crystal micropatterned via selective contact evaporation printing. The highly oriented lamellae with two degenerated orientations are explained by the crystallographic lattice match between the ferroelectric polymer and rubrene, giving rise to the enhanced ferroelectric polarization properties.